PENGARUH ADVERSITY QUOTIENT TERHADAP KEBERHASILAN USAHA PUSAT INDUSTRI KECIL MEDAN DENAI - Hutagalung, Bongsu; Hutagalung, Arif Qaedi (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2018)
This research was aimed to analyze the effect of control, ownership, reach, and endurance as a variable dimension of adversity quotient to the business success in Medan Denai. This type of research explanatory associative research. Based on the results of data processing with multiple linear regression analysis methods, the results of this study indicate that the influence of adversity quotient variables consisting of dimension control, ownership, reach, & endurance simultaneously positive and significant effect on the business success. Partially dimensional control and endurance positive and significant effect to the business success, meanwhile the ownership dimension and reach partially positive but not significant effect to the business success